(3eSGFd Ydj Hf LYaQs - (3Ydj Hf LYaQ GdUGObs
(3ChdgG (B:s
(3CNHQfG CMeO Hf ehSi Hf LYaQ Hf CHj GdYHGS (B... (3SCdJ CHj LYaQ Hf eMeO Yf QLd hGbY GeQCJg bHd WhGa GdfSGA(B...s
(3BNQgG (B:s
(3gd jUdM dg Cf jUdj Ch jUhe Yf HYV ehJGg(B. (3bGd(B: (3fYe, jUdj eG CMH hjLYd Pdc ddejJ EPG LYd Pdc dg(B. (3JeJs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc(B: (3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis